Carbon nanohorn-based ammonium polyphosphate composite flame-retardant textile fabric and preparation method thereof
By constructing an expanded flame retardant coating prepared by combining carbon nanoangles and ammonium polyphosphate on the surface of the textile, the problem of insufficient flame retardant performance of textiles is solved, and efficient flame retardant effect and self-extinguishing characteristics are achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411760809.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The flame retardant performance of existing textiles is insufficient and can easily cause fires. In addition, traditional flame retardant agents have poor application flexibility, low flame retardant efficiency and adverse effects on substrate performance.
The expanded flame retardant coating was prepared by combining carbon nanoangle and ammonium polyphosphate. The coating was constructed on the surface of the textile by spraying, and the physical barrier effect of carbon nanoangle and the expansion effect of ammonium polyphosphate were used to achieve synergistic flame retardant.
It significantly improves the flame retardant performance of textiles, imparts self-extinguishing characteristics to the fabric, reduces the occurrence of fire accidents and casualties, and has a simple process and mild conditions, which is suitable for large-scale industrial production.
Smart Images

Figure CN119571608A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame retardant materials, and in particular relates to a carbon nano-horn-based ammonium polyphosphate composite flame retardant textile and a preparation method thereof. Background Art
[0002] Textiles are widely used in people's daily lives, but most textiles are flammable materials. They melt, decompose and burn when heated, which can easily cause fires. In addition, they produce a lot of smoke and release toxic gases during the combustion process, which directly endangers human life and safety. Therefore, improving the flame retardant properties of textiles can greatly reduce the occurrence of fire accidents and casualties, which has very important social significance.
[0003] The common way to improve the flame retardant properties of textiles is to add flame retardants before the textiles are formed. This method has the disadvantages of poor application flexibility, low flame retardant efficiency, and deterioration of the processing properties, mechanical properties and UV aging resistance of the substrate. Compared with the method of directly adding flame retardants, constructing a flame retardant coating on the surface of textiles can effectively overcome the above defects. The flame retardant coating is easy to apply and can be constructed on the surface of the formed fabric by brushing, dipping or spraying. At the same time, the flame retardant coating covers the surface of the fabric and responds quickly to external flames before the polymer contacts the flame and thermal degradation occurs, exerting an efficient flame retardant effect. More importantly, the flame retardant coating will not destroy the internal structure of the fabric and has little effect on the comprehensive performance of the fabric. Therefore, constructing a flame retardant coating on the surface of the fabric is one of the most promising ways to improve its flame retardant properties.
[0004] At present, most flame retardant coatings are prepared based on traditional flame retardants (such as halogen or phosphorus flame retardants). Binders or film-forming agents are added to flame retardants by blending, grafting, coating or copolymerization to prepare uniformly dispersed coatings, and stable flame retardant coatings are prepared through coating and drying processes; or the flame retardant mechanism of fabrics deposits flame retardants on fabrics through mutual adsorption and deposition between ions, interaction between chemical bonds and bonding effects between molecules.
[0005] As an emerging method for flame retardant fabrics, layer-by-layer self-assembly is usually based on electrostatic interaction. The substrate is repeatedly and alternately immersed in positive and negative electrolytes, so that layers with positive and negative charges are accumulated on the surface of the substrate, so that the charge on the surface of the substrate is reversed after each immersion. CN105088791A discloses a fabric with flame retardant, antibacterial and conductive functions and a preparation method thereof, and a flame retardant fabric is prepared by layer-by-layer self-assembly. CN105155279A discloses a fabric with an intumescent flame retardant coating containing carbon nanotubes on the surface and a preparation method thereof, wherein at least one layer of a combined coating formed by a polyethyleneimine layer containing amino carbon nanotubes and an ammonium polyphosphate layer containing carboxylated carbon nanotubes is coated on both surfaces of the fabric to prepare a fabric with an intumescent flame retardant coating containing carbon nanotubes on the surface. Zhang et al. (Tao, Zhang, Hongqiang, et al. Construction of flame retardant nanocoating on ramie fabric via layer-by-layer assembly of carbon nanotube and ammonium polyphosphate. [J]. Nanoscale, 2013, 5 (7): 3013-21.) prepared ramie fabric flame retardant nanocoating by layer-by-layer assembly of carbon nanotube and ammonium polyphosphate. However, this technology also has some disadvantages, such as the repeated alternating immersion process easily causes mutual contamination between the assembly solutions, thereby wasting raw materials and reducing the flame retardant effect of the substrate.
[0006] Nanomaterials have high flame retardancy due to their unique "surface effect, volume effect and quantum effect", which is superior to traditional flame retardants such as ammonium polyphosphate. Carbon-based nanomaterials (graphene, carbon nanotubes, etc.) have outstanding carbon-rich structures, which makes them have extraordinary performance in terms of polymer carbonization quality, thermal stability and mechanical properties. However, the application of carbon-based nanomaterials is difficult. For example, carbon nanotubes are expensive, have certain toxicity, and the preparation process requires the addition of catalysts, which makes the process complicated.
[0007] Carbon nanotubes have been widely used in the field of flame retardancy in the past few decades. Considering that the development of low-cost carbon-based nano flame retardants with controlled dispersion, low loading in polymer matrix and excellent performance is still the future direction, the improvement of carbon-based nano flame retardant technology is still necessary. Summary of the invention
[0008] In order to solve the above technical problems, one of the objectives of the present invention is to provide a method for preparing a carbon nano-horn-based ammonium polyphosphate composite flame-retardant textile.
[0009] The present invention adopts the following technical solutions:
[0010] A method for preparing a carbon nano-horn-based ammonium polyphosphate composite flame-retardant textile comprises the following steps:
[0011] S1. The textile is immersed in a sodium hydroxide solution of a set concentration. After the immersion is completed, the textile is washed until the pH value of the textile washing wastewater is neutral, and the textile is dried and set aside;
[0012] S2. Prepare an ammonium polyphosphate solution of a set concentration, adjust the solution pH to 10-11, add the single-walled carbon nanohorns to the ammonium polyphosphate solution, and ultrasonically treat to obtain a spray solution;
[0013] S3. The spray liquid is adjusted to 1mL:9cm 2 The ratio of is evenly sprayed on the surface of the textile, and the completion of spraying on the front and back sides of the textile is recorded as one cycle. After each cycle, the textile is dried. The cycle spraying is repeated at least 6 times to obtain a carbon nano-horn-based ammonium polyphosphate composite flame-retardant textile.
[0014] Preferably, in step S2, 1 g of ammonium polyphosphate is added to 100 mL of deionized water, the degree of polymerization of the ammonium polyphosphate is greater than 1000, and the mass ratio of the single-walled carbon nanohorns to the ammonium polyphosphate is (0.1-0.2):1.
[0015] Preferably, in step S1, the concentration of the sodium hydroxide solution is 0.5-1 mol / L.
[0016] Preferably, the spraying distance is 5 cm.
[0017] Preferably, in step S1, the drying temperature is 60°C.
[0018] Preferably, in step S3, the drying temperature is 50-90°C.
[0019] Preferably, the textile is any one of cotton, linen, polyester and nylon, or a blend of at least two of them.
[0020] The second object of the present invention is to provide a fire-proof fabric, the surface of which is provided with a carbon nanohorn-based ammonium polyphosphate composite flame-retardant coating, the flame-retardant coating has a thickness of 40 μm and is composed of ammonium polyphosphate and single-walled carbon nanohorns, and the usage ratio of the ammonium polyphosphate to the single-walled carbon nanohorns is 10:(1~2).
[0021] Preferably, the fabric is any one of cotton, linen, polyester and nylon, or a blend of at least two of them.
[0022] The beneficial effects of the present invention are:
[0023] 1) For the first time, a new type of carbon nanomaterial, single-walled carbon nanohorn, was used as a member of the flame retardant system and compounded with ammonium polyphosphate to prepare an intumescent flame retardant coating with high flame retardant effect. In the coating, carbon nanohorn acts as a carbon source, and ammonium polyphosphate is used as a gas source and acid source. Since the carbon nanohorn solution itself is negatively charged, ammonium polyphosphate will be ionized after being dissolved in water to form free ammonium ions and phosphate ions. Among them, the ammonium ions are positively charged and will be electrostatically adsorbed with the single-walled carbon nanohorn, so that the ammonium ions are closely connected to the edge of the carbon nanohorn, forming a carbon nanohorn-based ammonium polyphosphate micro-nanostructure coating. In the coating, ammonium polyphosphate and single-walled carbon nanohorn are connected by hydrogen bonds, and there is a van der Waals force between the two. The hydrogen bonds and van der Waals forces promote the interaction between ammonium polyphosphate and carbon nanohorns during the layer-by-layer self-assembly process. These non-covalent interactions contribute to the stability and structural integrity of the layer.
[0024] 2) The physical barrier effect of carbon nanohorns in the coating and the expansion effect of ammonium polyphosphate have a synergistic flame retardant effect, and the flame retardant properties of textiles can be further improved after compounding: the carbon nanohorn / ammonium polyphosphate coating provided by the present invention can give the fabric a flame retardant mechanism with self-extinguishing properties, that is, in the early stage of cotton fabric combustion, ammonium polyphosphate plays a catalytic carbonization effect, thermally degrades in advance to produce polyphosphoric acid and ammonia, and catalyzes the dehydration and carbonization of cotton fabric and carbon nanohorns. In addition, the presence of ammonia dilutes the oxygen concentration; in the later stage of combustion, due to the excellent thermal stability of carbon nanohorns at high temperatures, it can improve the carbonization effect, improve the stability of the carbon layer, and act as an effective physical barrier. The synergistic flame retardant effect between ammonium polyphosphate and carbon nanohorns protects the cotton fabric from further erosion by the flame and achieves self-extinguishing away from the fire.
[0025] 3) Compared with carbon materials such as carbon nanotubes or graphene, the carbon nanohorn raw material used in the present invention has a simple preparation method, does not require a catalyst in the preparation process, and does not require the use of fluorine-containing compounds and halogen-containing flame retardants. It has high purity and yield, a wide source, is non-toxic and harmless, and is in line with the development direction of safety and environmental protection.
[0026] 4) The flame-retardant coated fabric can be prepared by a simple one-pot method, which has the advantages of simple process, mild conditions, short time consumption and no need for specific instruments and equipment compared with the prior art, and is conducive to large-scale industrial production.
[0027] 5) The flame retardant textile provided by the present invention has excellent flame retardant properties, the amount of residual carbon after the fabric is burned increases, and except for some shrinkage and bubbles on the surface of the residual carbon, the geometric structure of the fabric matrix is not destroyed. It has broad application prospects in the fields of protective clothing, home decoration, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The transmission electron microscope (a) and thermogravimetric curve (b) of the raw material single-walled carbon nanohorn in the present invention are shown.
[0029] Figure 2 These are scanning electron microscope images of the pure cotton fabric in the test, the carbon nanohorn / ammonium polyphosphate @ cotton fabric in Example 1, the ammonium polyphosphate @ cotton fabric in Comparative Example 1, and the carbon nanohorn @ cotton fabric in Comparative Example 2.
[0030] Figure 3 The vertical combustion test results of the pure cotton fabric in the experiment, the carbon nanohorn / ammonium polyphosphate @ cotton fabric in Example 1, the ammonium polyphosphate @ cotton fabric in Comparative Example 1, and the carbon nanohorn @ cotton fabric in Comparative Example 2 are shown.
[0031] Figure 4 It is a comparison chart of the limiting oxygen index (LOI) and damage length of the pure cotton fabric in the test, the carbon nanohorn / ammonium polyphosphate @ cotton fabric in Example 1, the ammonium polyphosphate @ cotton fabric in Comparative Example 1, and the carbon nanohorn @ cotton fabric in Comparative Example 2.
[0032] Figure 5 The scanning electron microscope images of the residues after vertical combustion of the pure cotton fabric in the test, the carbon nanohorn / ammonium polyphosphate @ cotton fabric in Example 1, the ammonium polyphosphate @ cotton fabric in Comparative Example 1, and the carbon nanohorn @ cotton fabric in Comparative Example 2.
[0033] Figure 6 1 and 2 are heat release rate curves of the residues after vertical combustion of the pure cotton fabric in the test, the carbon nanohorn / ammonium polyphosphate @ cotton fabric in Example 1, the ammonium polyphosphate @ cotton fabric in Comparative Example 1, and the carbon nanohorn @ cotton fabric in Comparative Example 2. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is described in more detail below in conjunction with the embodiments and drawings.
[0035] The fabric used in this experiment (179g / m 2 ) is produced by Shaoxing Aobang Technology Co., Ltd., the product name is AL-plain cotton and linen, and the composition is: 65% polyester and 35% cotton.
[0036] The carbon nanohorns referred to in this experiment are all single-walled carbon nanohorns. The single-walled carbon nanohorns used in this experiment were provided by the team of Professor Liang Feng of Kunming University of Science and Technology. The preparation method is: after heating the graphite rod to 1000℃, under the condition of air atmosphere and argon negative pressure of 70kPa, argon gas is directly injected into the arc discharge area through the hole of the cathode graphite rod, and the current is controlled to 200A to prepare it by DC arc discharge method (DC arc-discharge).
[0037] Example 1
[0038] A carbon nano-horn-based ammonium polyphosphate composite flame-retardant textile is prepared by:
[0039] S1. Prepare a 0.5 mol / L sodium hydroxide solution, place the fabric in the solution, and soak it at 80°C for 1 hour for mercerization. After mercerization, the crystallinity of the fabric decreases and the amorphous area increases, so the adsorption and chemical reaction properties of the fabric to substances are improved, and it is easy to combine with single-walled carbon nanohorns. After soaking, wash with anhydrous ethanol and deionized water for multiple times until the washing liquid is neutral, and then place the fabric in a 60°C oven to dry for use.
[0040] S2. Weigh 1 g of ammonium polyphosphate and disperse it in 100 mL of deionized water to obtain an ammonium polyphosphate solution. Use NaOH to adjust the pH value of the solution to 10. Then add 0.15 g of single-walled carbon nanohorns to the ammonium polyphosphate solution. After sufficient stirring, ultrasonic treatment is performed in an ultrasonic device for 15 minutes to obtain a uniform spray solution.
[0041] S3. Use the spraying method to spray the spraying liquid evenly on the surface of the fabric at a distance of 5 cm from the fabric. The spraying area on one side of the fabric is 36 cm 2 4 mL of spray liquid was used on each side, and a desktop ultrasonic precision sprayer was used for spraying; after spraying on each side of the fabric, it was placed in an oven at 80°C and dried for 10 min; the spraying of the front and back sides of the fabric was completed as one cycle, and a total of 6 cycles of spraying were performed to obtain carbon nanohorns / ammonium polyphosphate@fabric (0.15).
[0042] Example 2
[0043] A carbon nano-horn-based ammonium polyphosphate composite flame-retardant textile is prepared by:
[0044] S1. Prepare a 0.5 mol / L sodium hydroxide solution, place the fabric in the solution, and soak it at 80°C for 1 hour for mercerization treatment to enhance the gloss, surface adhesion and dimensional stability of the fabric. After soaking, wash it with anhydrous ethanol and deionized water for multiple times until the washing liquid is neutral, and then place the fabric in a 60°C oven to dry for use.
[0045] S2. Weigh 1 g of ammonium polyphosphate and disperse it in 100 mL of deionized water to obtain an ammonium polyphosphate solution. Use NaOH to adjust the pH value of the solution to 10. Then add 0.1 g of single-walled carbon nanohorns to the ammonium polyphosphate solution. After sufficient stirring, ultrasonic treatment is performed in an ultrasonic device for 15 minutes to obtain a uniform spray solution.
[0046] S3. Use the spraying method to spray the spraying liquid evenly on the surface of the fabric at a distance of 5 cm from the fabric. The spraying area on one side of the fabric is 36 cm 24 mL of spray liquid was used on each side, and a desktop ultrasonic precision sprayer was used for spraying; after spraying on each side of the fabric, it was placed in an oven at 80°C and dried for 10 min; the completion of spraying on the front and back sides of the fabric was counted as one cycle, and a total of 6 cycles of spraying were performed to obtain carbon nanohorns / ammonium polyphosphate@fabric (0.1).
[0047] Example 3
[0048] A carbon nano-horn-based ammonium polyphosphate composite flame-retardant textile is prepared by:
[0049] S1. Prepare a 0.5 mol / L sodium hydroxide solution, place the fabric in the solution, and soak it at 80°C for 1 hour for mercerization treatment to enhance the gloss, surface adhesion and dimensional stability of the fabric. After soaking, wash it with anhydrous ethanol and deionized water for multiple times until the washing liquid is neutral, and then place the fabric in a 60°C oven to dry for use.
[0050] S2. Weigh 1 g of ammonium polyphosphate and disperse it in 100 mL of deionized water to obtain an ammonium polyphosphate solution. Use NaOH to adjust the pH value of the solution to 10. Then add 0.2 g of single-walled carbon nanohorns to the ammonium polyphosphate solution. After sufficient stirring, ultrasonic treatment is performed in an ultrasonic device for 15 minutes to obtain a uniform spray solution.
[0051] S3. Use the spraying method to spray the spraying liquid evenly on the surface of the fabric at a distance of 5 cm from the fabric. The spraying area on one side of the fabric is 36 cm 2 4 mL of spray liquid was used on each side, and a desktop ultrasonic precision sprayer was used for spraying; after spraying on each side of the fabric, it was placed in an oven at 80°C and dried for 10 minutes; the completion of spraying on the front and back sides of the fabric was counted as one cycle, and a total of 6 cycles of spraying were performed to obtain carbon nanohorns / ammonium polyphosphate@fabric (0.2).
[0052] Comparative Example 1
[0053] S1. Prepare a 0.5 mol / L sodium hydroxide solution, place the fabric in the solution, and soak it at 80°C for 1 hour for mercerization to enhance the gloss, surface adhesion and strength of the fabric. After soaking, wash it with anhydrous ethanol and deionized water for multiple times until the washing liquid is neutral, and then place the fabric in a 60°C oven to dry for use.
[0054] S2. Weigh 1 g of ammonium polyphosphate and disperse it in 100 mL of deionized water to obtain an ammonium polyphosphate solution. Adjust the pH value of the solution to 10 with NaOH, stir thoroughly and ultrasonically treat in an ultrasonic device for 15 min to obtain a uniform spray solution.
[0055] S3. Use the spraying method to spray the spraying liquid evenly on the surface of the fabric at a distance of 5 cm from the fabric. The spraying area on one side of the fabric is 36 cm 24 mL of spray liquid was used on each side, and a desktop ultrasonic precision sprayer was used for spraying; after spraying on each side of the fabric, it was placed in an oven at 80°C and dried for 10 minutes; the completion of spraying on the front and back sides of the fabric was recorded as one cycle, and a total of 6 cycles of spraying were performed to obtain ammonium polyphosphate @ fabric.
[0056] Comparative Example 2
[0057] S1. Prepare a 0.5 mol / L sodium hydroxide solution, place the fabric in the solution, and soak it at 80°C for 1 hour for mercerization to enhance the gloss, surface adhesion and strength of the fabric. After soaking, wash it with anhydrous ethanol and deionized water for multiple times until the washing liquid is neutral, and then place the fabric in a 60°C oven to dry for use.
[0058] S2. Weigh 1 g of single-walled carbon nanohorns and disperse them in 100 mL of deionized water. Then add 0.5 g of sodium dodecyl sulfate to make the single-walled carbon nanohorns more easily dispersed in the deionized water. After sufficient stirring, ultrasonic treatment is performed in an ultrasonic device for 15 minutes to obtain a uniform spray liquid.
[0059] S3. Use the spraying method to spray the spraying liquid evenly on the surface of the fabric at a distance of 5 cm from the fabric. The spraying area on one side of the fabric is 36 cm 2 4 mL of spray liquid was used on each side, and a desktop ultrasonic precision sprayer was used for spraying; after spraying on each side of the fabric, it was placed in an oven at 80°C and dried for 10 minutes; the completion of spraying on the front and back sides of the fabric was counted as one cycle, and a total of 6 cycles of spraying were performed to obtain carbon nanohorn@fabric.
[0060] 1. Analysis
[0061] Transmission electron microscopy and thermogravimetric analysis were used to preliminarily characterize the morphology, structure and thermal stability of single-walled carbon nanohorns. Figure 1 As shown in (a), the sample is a typical "dahlia"-shaped single-walled carbon nanohorn, consisting of a tube with a conical top, and its cone angle is 20°. The average diameter of the tubular part of the carbon nanohorn is 2-5nm, and the top of the cone contains pentagonal, heptagonal and hexagonal carbon rings. Figure 1 (b) The thermogravimetric curve shows that the residual mass of carbon nanohorns is 82.72% at 700°C, indicating that carbon nanohorns have excellent carbon-forming ability and are almost not decomposed at high temperatures.
[0062] Figure 2Scanning electron microscope images of untreated fabric (a1-a3), carbon nanohorn / ammonium polyphosphate@fabric (b1-b3), ammonium polyphosphate@fabric (c1-c3) and carbon nanohorn@fabric (d1-d3) in the experiment are shown. From a1-a3, it can be seen that the surface of pure cotton fabric is smooth and neat; from c1-c3, it can be seen that the surface of fabric treated with ammonium polyphosphate becomes rough, and adjacent fibers are connected to each other, which proves that ammonium polyphosphate has been successfully and evenly attached to the surface of cotton fabric; from d1-d3, it can be seen that due to the easy agglomeration of carbon nanohorns, the surface of cotton fabric directly treated by them is covered with incomplete and broken coatings. From b1-b3, a uniform and dense coating can be observed, and adjacent fibers are completely connected and covered by the coating, indicating that the carbon nanohorn / ammonium polyphosphate coating is successfully attached to the surface of the fabric. Compounding carbon nanohorns with ammonium polyphosphate in an alkaline environment can obtain a uniform spray solution, and the surface of the carbon nanohorns is coated with a thin film formed by ammonium polyphosphate, which helps to fix the nanoparticles on the surface of the fabric.
[0063] Energy spectrum analysis was performed on untreated fabrics (a1-a3), carbon nanohorn / ammonium polyphosphate @ fabrics (b1-b3), ammonium polyphosphate @ fabrics (c1-c3) and carbon nanohorn @ fabrics (d1-d3) to determine the elemental distribution of the four groups of samples. Compared with the untreated fabrics (a1-a3) containing only C and O elements, carbon nanohorn @ fabrics (d1-d3) are composed of C, O and N elements; in addition, ammonium polyphosphate @ fabrics (c1-c3) and carbon nanohorn / ammonium polyphosphate @ fabrics (0.15) (b1-b3) contain P and N elements in addition to C and O, which also fully demonstrates that the coating is successfully deposited on cotton fabrics. The elemental composition of the four groups of samples is shown in Table 1 below.
[0064] Table 1 Elemental composition of four groups of samples
[0065]
[0066]
[0067] 2. Flame retardant test
[0068] Vertical burning test and LOI test were carried out on untreated fabric, carbon nanohorn / ammonium polyphosphate@fabric, ammonium polyphosphate@fabric and carbon nanohorn@fabric.
[0069] like Figure 3-Figure 4As shown in the figure, the untreated fabric and carbon nanohorn@fabric have high flammability, with LOI of 17.5±0.53% and 18.3±0.55%, respectively, and almost no residue after burning. In contrast, carbon nanohorn / ammonium polyphosphate@fabric (0.15) and ammonium polyphosphate@fabric significantly enhance the flame retardant properties of the fabric and have self-extinguishing properties. Among them, the damage length of carbon nanohorn / ammonium polyphosphate@fabric (0.15) and ammonium polyphosphate@fabric decreased from 30±0.01% to 6.5±0.06%cm and 8.4±0.08%cm, respectively. Except for partial carbonization, the fabric maintained its original orthogonal structure. At the same time, the LOI values of carbon nanohorn / ammonium polyphosphate@fabric (0.15) and ammonium polyphosphate@fabric increased to 27.5±0.83% and 25±0.75%, respectively. The fabrics are difficult to be easily ignited, and there is no smoldering time. At the same time, they have the characteristics of self-extinguishing away from the fire, and can reach UL-94V-0 level. This result further indicates that single-walled carbon nanohorns have a synergistic effect on the ammonium polyphosphate flame retardant system.
[0070] Figure 5 Figure 2 is the scanning electron microscope image of the residues of the four groups of samples after vertical combustion. Table 2 is the elemental composition of the residues.
[0071] It can be seen that the pure fabric is completely burned, leaving only a few fragile ashes. Compared with pure fabric, the carbon nanohorn @ fabric is relatively lightly damaged after burning, and the cotton fiber strip structure can still be clearly seen. After the ammonium polyphosphate @ fabric is burned, long and thin stripes and wrinkles appear on the surface of the residual carbon, while there are a large number of bubbles on the surface of the residual carbon of the carbon nanohorn / ammonium polyphosphate @ fabric. This is mainly because the composite flame retardant liquid containing P and N elements plays an expanding flame retardant role during the combustion process, forming an expanded carbon layer on the surface of the fabric. The formed carbon layer can effectively reduce the volatilization of combustible gases and isolate the transfer of oxygen and heat, thereby achieving a flame retardant effect.
[0072] Table 2 Elemental composition of the residue after vertical combustion
[0073]
[0074]
[0075] The results of energy spectrum analysis show that the N content of carbon nanohorns / ammonium polyphosphate @ fabric and ammonium polyphosphate @ fabric after combustion shows opposite trends. The N content of the former decreases from 7.75% to 1.87%, while the N content of the latter increases from 1.42% to 3.91%. This shows that the addition of carbon nanohorns promotes the dehydration of ammonium polyphosphate and the carbonization of cotton fibers, accelerates the generation of ammonia, and thus causes the free radicals on which combustion depends to combine and terminate the chain reaction. In addition, free radicals may also collide with the particles that make up the bubbles and combine with each other to form stable molecules, causing the chain reaction to be interrupted. This shows that the addition of carbon nanohorns can not only achieve condensed phase flame retardancy and play the role of a physical barrier, but also may play a flame retardant role in the gas phase, so that the fabric can achieve a self-extinguishing effect in vertical combustion.
[0076] In order to verify the flame retardant effect of carbon nanohorns, cone calorimetry tests (performed in accordance with standard ISO 5660-1) were carried out on untreated fabric, carbon nanohorns / ammonium polyphosphate@fabric, ammonium polyphosphate@fabric and carbon nanohorns@fabric, respectively. The cone calorimetry characteristic parameters are shown in Table 3.
[0077] Table 3 Cone calorimetry characteristic parameters of each sample
[0078]
[0079] The heat release rate curves of each sample are shown in Figure 6 The peak heat release rate (pHRR) is one of the important fire characteristic parameters of materials. The smaller its value, the smaller the fire hazard. Figure 6 It can be seen that the pHRR of pure fabric is higher, while the pHRR decreases after adding single-walled carbon nanohorns to the ammonium polyphosphate system. The decrease rate of the group adding 0.15% carbon nanohorns is as high as 92.2%. This is mainly because carbon nanohorns can form an insulating carbon layer during the combustion process, reducing the release of combustible volatile substances. Similarly, after adding 1% ammonium polyphosphate and carbon nanohorns separately, the pHRR of ammonium polyphosphate@fabric and carbon nanohorns@fabric increased from 284.41kW / m 2 They dropped to 26.18kW / m 2 and 248.95kW / m 2 This shows that carbon nanohorns are not effective when used alone as flame retardants, but can be combined with phosphorus and nitrogen flame retardants to effectively assist flame retardancy. This is mainly because ammonium polyphosphate decomposes into ammonia and polyphosphoric acid when heated. Polyphosphoric acid catalyzes the decomposition of fibers into carbon and water, reducing the heat generated during the combustion process and playing a chemical barrier effect; in addition, the carbon layer formed by carbon nanohorns has a physical barrier effect on heat and oxygen. The interaction between the two ultimately enhances the residual carbon structure and reduces the heat release rate, thereby improving the flame retardant effect of the fabric.
[0080] From Table 3 and Figure 6It can also be seen that with the increase of carbon nanohorn content, the pHRR of carbon nanohorn / ammonium polyphosphate@fabric shows a downward trend. When the carbon nanohorn content is greater than 0.15%, the pHRR increases. This is because the high content of carbon nanohorns is poorly dispersed in ammonium polyphosphate, which affects the carbon layer structure formed after combustion and weakens its physical barrier effect. Therefore, when the addition amount of carbon nanohorns is 0.15%, it can synergize with ammonium polyphosphate to significantly improve the flame retardant properties of the fabric.
[0081] Different carbon materials have different flame retardant mechanisms. Carbon nanotubes can overlap on the polymer surface to form a barrier carbon layer with a network structure. The barrier layer can prevent external heat and oxygen from reaching the polymer surface, and can also prevent the combustibles produced by polymer degradation from escaping into the air. In addition, the presence of the barrier layer can inhibit the thermal motion of polymer molecular chains, increase the viscosity of the composite system, and delay the degradation of the polymer; the expanded graphite generated by the thermal expansion of expandable graphite (EG) can cover the surface of the substrate, protect the substrate, isolate heat and mass transfer, reduce the thermal degradation rate, and achieve the effect of isolating the fire source, delaying or interrupting the spread of fire; the flame retardant mechanism of graphene comes from its unique two-dimensional flake morphology, which effectively changes the diffusion path of the pyrolysis products of combustibles, and at the same time, graphene can promote the formation of a compact, uniform and dense protective carbon layer. Carbon nanohorns are spherical aggregates self-assembled from thousands of monodisperse conical carbon tubes. The unique conical structure gives them high thermal stability. The present invention finds that during the combustion of polymers, carbon nanohorns are not easily decomposed at high temperatures due to their high thermal stability and excellent charring ability. Therefore, they improve the carbonization effect and the stability of the char layer in the later stage of fabric combustion, acting as an effective physical barrier and combining with the characteristics of ammonium polyphosphate to achieve flame retardancy.
[0082] According to reports, patent CN105155279A discloses a method for preparing a fabric with an intumescent flame-retardant coating containing carbon nanotubes on the surface. The coated cotton fabric in the embodiment does not disclose the afterflaming time and smoldering time in the vertical combustion test, but the best set of experiments showed that the carbon residue rate of the coated cotton fabric was 27.3% at 700°C; while in a nitrogen atmosphere, the carbon residue rate of the coated cotton fabric was 47.4%, and the carbon residue length was 4.5 cm. The area ratio of the D peak to the G peak of the carbon residue of the coated cotton fabric after combustion was 3.22, and the carbon residue length of the flame retardant performance of the coated cotton fabric after washing 30 times according to the standard was 8.1 cm, which has a self-extinguishing effect. Zhang et al. (Tao, Zhang, Hongqiang, et al. Construction of flameretardant nanocoating on ramie fabric via layer-by-layer assembly of carbon nanotube and ammonium polyphosphate. [J]. Nanoscale, 2013, 5 (7): 3013-21.) constructed a new flame retardant nanocoating by alternately adsorbing polyelectrolyte amino-functionalized multi-walled carbon nanotubes and ammonium polyphosphate onto flexible porous ramie fabric. Compared with the original sample, the PHRR and THR values of the treated fabric decreased with the increase of the number of double layers (0.1 mg mL -1 / 1.0wt%) 20 The PHRR and THR values of the original ramie fabric are 107 W·g lower than those of the original ramie fabric. -1 and 2.2 kJ·g-1, coated with a concentration of 0.5 mg mL -1 PHRR and THR values of ramie fabrics with MWNT-NH2 (0.5 mg mL -1 / 1.0wt%) 20 Ratio (0.1 mg mL -1 / 1.0wt%) 20 Low 9W·g -1 and 0.7 kJ·g -1 . The outstanding effect of the experiment conducted in this patent is that at 700℃, the residual carbon rate of the coated cotton fabric in nitrogen and air atmosphere is 35.8% and 25.0% respectively, the damaged length of the coated cotton fabric after burning is 6.5cm, and the area ratio of the D peak to the G peak of the carbon residue of the coated cotton fabric after burning is 0.34, and the flame retardant effect is significantly better than the former. Compared with pure cotton fabric, the PHRR and THR values of the treated fabric are significantly reduced, and the PHRR and THR values of the fabric with 0.15g carbon nanohorns added are 262W·g lower than those of the pure fabric. -1 and 4.7 kJ·g -1The results obtained by this method are better than those of the above-mentioned flame retardant materials.
[0083] It should be noted that the fabric used in the embodiment is only selected as an experiment. After the fabric is mercerized, it swells in a concentrated alkali solution, and the hydrogen bonds between the macromolecular chains are broken up, which relieves the internal stress stored in the fabric. By stretching, the macromolecules are oriented and arranged, and new molecular bonds are established in the new position, and the intermolecular force is larger than before swelling. Finally, alkali is removed under tension, and the hydrogen bonds between the oriented fibers are fixed. At this time, the fibers are in a lower energy state, so the fabric size is stable. Similar properties are mostly available for other types of textiles, so this method is also applicable to other textiles.
[0084] The above implementation modes are only used to illustrate the technical solutions of the present invention, but not to limit the present invention. Although the present invention has been described in detail with reference to the above implementation modes, those skilled in the art should understand that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon nano-horn-based ammonium polyphosphate composite flame-retardant textile, characterized in that: The following steps are involved: S1. The textile is immersed in a sodium hydroxide solution of a set concentration. After the immersion is completed, the textile is washed until the pH value of the textile washing wastewater is neutral, and the textile is dried and set aside; S2. Prepare an ammonium polyphosphate solution of a set concentration, adjust the solution pH to 10-11, add the single-walled carbon nanohorns to the ammonium polyphosphate solution, and ultrasonically treat to obtain a spray solution; S3. The spray liquid is adjusted to 1mL:9cm 2 The ratio of is evenly sprayed on the surface of the textile, and the completion of spraying on the front and back sides of the textile is recorded as one cycle. After each cycle, the textile is dried. The cycle spraying is repeated at least 6 times to obtain a carbon nano-horn-based ammonium polyphosphate composite flame-retardant textile.
2. The method for preparing a carbon nano-horn-based ammonium polyphosphate composite flame-retardant textile according to claim 1, characterized in that: In the step S2, 1 g of ammonium polyphosphate is added into 100 mL of deionized water, the degree of polymerization of the ammonium polyphosphate is greater than 1000, and the mass ratio of the single-walled carbon nanohorns to the ammonium polyphosphate is (0.1-0.2):
1.
3. The method for preparing a carbon nano-horn-based ammonium polyphosphate composite flame-retardant textile according to claim 1, characterized in that: In step S1, the concentration of the sodium hydroxide solution is 0.5-1 mol / L.
4. The method for preparing a carbon nano-horn-based ammonium polyphosphate composite flame-retardant textile according to claim 1, characterized in that: In the step S1, the drying temperature is 60°C.
5. The method for preparing a carbon nano-horn-based ammonium polyphosphate composite flame-retardant textile according to claim 1, characterized in that: In step S3, the drying temperature is 50-90°C.
6. The method for preparing a carbon nano-horn-based ammonium polyphosphate composite flame-retardant textile according to claim 1, characterized in that: The textile is any one of cotton, linen, polyester and nylon, or a blend of at least two of them.
7. A fireproof fabric, characterized in that: The surface of the fabric is provided with a carbon nanohorn-based ammonium polyphosphate composite flame retardant coating, the thickness of the flame retardant coating is 40 μm, and it is composed of ammonium polyphosphate and single-walled carbon nanohorns, and the usage ratio of the ammonium polyphosphate to the single-walled carbon nanohorns is 10:(1-2).
8. A fireproof fabric according to claim 7, characterized in that: The fabric is any one of cotton, linen, polyester and nylon, or a blend of at least two of them.
Citation Information
Patent Citations
Fabric with anti-flaming, anti-microbial and electric conducting functions and preparation method thereof
CN105088791A
Fabric provided with expansive type flame-retardant coatings including carbon nano tubes on surfaces and preparation method thereof
CN105155279A
Self-extinguishing flame-retardant cotton fabric and preparation method and application thereof
CN109944070A